Salmonella Typhimurium in livestock in Great Britain – trends observed over a 32-year period. Issue 4 (8th February 2018) - Mueller-Doblies, D.; Speed, K. C. R.; Kidd, S.; Davies, R. H.
Abstract: In this retrospective study, we describe and analyse Salmonella data from four livestock species in Great Britain between 1983 and 2014, focusing on Salmonella Typhimurium. A total of 96 044 Salmonella isolates were obtained during the study period. S . Typhimurium was the predominant serovar isolated from cattle and pigs and represented 40.7% (18 455/45 336) and 58.3% (4495/7709) of isolates from these species respectively, while it only accounted for 6.7% (2114/31 492) of chicken isolates and 8.1% (926/11 507) of turkey isolates. Over the study period, DT104 was the most common phage type in all four species; however, DT104 peaked in occurrence between 1995 and 1999, but is currently rare. Monophasic strains of S. Typhimurium represented less than 3% of all Salmonella isolates in cattle and chickens in 2014, but accounted for 10.4% of all turkey isolates and 39.0% of all pig isolates in the same year. Salmonella isolates were tested for their in vitro susceptibility to 16 antimicrobials. Antimicrobial resistance of S. Typhimurium isolates is largely influenced by the dominance of specific phage types at a certain time, which are commonly associated with particular resistance patterns. Changes in resistance patterns over time were analysed and compared between species.